Amstal expression patterns in the Qur'an and Hadith and their application in Arabic learning - Oman Karya Suhada; Jimatul Arrobi (Indonesian Journal of Arabic Studies, 2022)
Abstract : This study discusses the pattern of the expression "amstal" in the Qur'an and Hadith. The purpose of this study is to find out the pattern of the expression "amstal" in the Qur'an and Hadith, the characteristics, and aspects of the similarities between the two and its application in learning Arabic. This research method is descriptive analysis. The conclusion of this study is that the pattern of the phrase "amstal" in the Qur'an consists of patterns 1). Ø¶Ø±Ø¨ Ø§Ù„Ù„Ù‡ Ù…Ø«Ù„Ø§ ÙƒØ°Ø§ ÙˆÙƒØ°Ø§ Ù‡Ù„ ÙŠØ³ØªÙˆÙŠØ§Ù†ØŸ ). Ø¶Ø±Ø¨ Ø§Ù„Ù„Ù‡ Ù…Ø«Ù„Ø§ Ù„ÙƒØ°Ø§ ÙƒØ°Ø§3 ). Ù…Ø«Ù„ ÙƒØ°Ø§ ÙƒÙ…Ø«Ù„ ÙƒØ°Ø§4). Ù…Ø«Ù„ ÙƒØ°Ø§ ÙƒÙƒØ°Ø§.5). Ø¥Ù†Ù‘ Ù…Ø«Ù„ ÙƒØ°Ø§ ÙƒÙ…Ø«Ù„ ÙƒØ°Ø§ØŒ.(6 ). ÙƒØ°Ø§ ÙƒÙ…Ø«Ù„ ÙƒØ°Ø§7. Ù…Ø«Ù„ ÙƒØ°Ø§... while the expression pattern in the hadith consists of ( 1). Ù…Ø«Ù„ ÙƒØ°Ø§ Ù…Ø«Ù„ØŒ 2). Ù…Ø«Ù„ ÙƒØ°Ø§ ÙƒÙ…Ø«Ù„ ÙƒØ°Ø§ØŒ 3). Ù…Ø«Ù„ ÙƒØ°Ø§ ÙƒÙƒØ°Ø§ØŒ 4 ÙƒØ°Ø§ ÙƒÙ…Ø§ ÙƒØ°Ø§ØŒ , Â (5). Ù…Ø«Ù„ ÙƒØ°Ø§ ÙˆÙ…Ø«Ù„ ÙƒØ°Ø§ ÙƒÙ…Ø«Ù„ ÙƒØ°Ø§ØŒ 6). Ø¥Ù†Ù‘ Ù…Ø«Ù„ ÙƒØ°Ø§ ÙƒÙ…Ø«Ù„ ÙƒØ°Ø§ØŒ 7). Ù…Ø«Ù„ ÙƒØ°Ø§ ÙˆÙ…Ø«Ù„ ÙƒØ°Ø§. The characteristics of the expression patterns in the Qur'an are â€œ Ø¶Ø±Ø¨ Ø§Ù„Ù„Ù‡ Ù…Ø«Ù„Ø§ ÙƒØ°Ø§ ÙˆÙƒØ°Ø§â€ and in hadith are â€œÙ…Ø«Ù„ ÙƒØ°Ø§ ÙˆÙ…Ø«Ù„ â€œ and the point of equality of the two is â€œÙ…Ø«Ù„ ÙƒØ°Ø§ ÙƒÙƒØ°Ø§â€ As for its application in learning Arabic through the practice of language patterns in the text of the Qur'an and hadith in the form of amstal expression patterns that allow students to develop the uslub into several examples such as.